Necrocapitalism - Bobby Banerjee, Subhabrata (Organization studies, 2008)
In this paper I develop the concept of necrocapitalism, defined as contemporary forms of organizational accumulation that involve dispossession and the subjugation of life to the power of death. I examine how different forms of power — institutional, material, and discursive — operate in the political economy and the violence and dispossession that result. I describe some contemporary forms of organizational accumulation that involve dispossession and death and could therefore be described as necrocapitalist practices — for example, the impact of the resources industry in developing countries and the privatization of war and the military. I conclude by discussing some possibilities of resistance and outlining directions for future research.